The Screaming Thing: A Material Ecocritical Exploration of Trauma in Aleksandrs Pelēcis’s Poems - Ostups, Artis (Respectus Philologicus, 2024)
This article investigates the intersection of trauma studies and new materialism, offering a fresh perspective on human trauma through the prism of nonhuman forces. Drawing inspiration from material ecocriticism, a paradigm that evolved from materialist and posthumanist ideas and has not yet been brought into contact with trauma studies, the article underscores the significance of considering the embodiment of experience, thus arriving at an extended notion of trauma. This new theoretical framework is tested by examining the testimonial poetry of Latvian writer Aleksandrs Pelēcis, who was deported to Siberia by Soviet authorities in 1946. His poems employ inanimate objects and animals to create metonymical and metaphorical connections between human and nonhuman actors within the context of long exile. By illuminating a shared experiential space, Pelēcis manages to project and diffract traumatic feelings and memories, thus making them more comprehensible to his readers. This, in turn, places trauma studies on a trajectory away from the traditional conceptualisation of the inexpressible and the awkward.
Keywords: Trauma studies; New materialism; Material ecocriticism; Aleksandrs Pelēcis